2016
DOI: 10.4103/1735-1995.193178
|View full text |Cite
|
Sign up to set email alerts
|

Do symbiotic and Vitamin E supplementation have favorite effects in nonalcoholic fatty liver disease? A randomized, double-blind, placebo-controlled trial

Abstract: Background:Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in the world. Oral administration of symbiotic and Vitamin E has been proposed as an effective treatment in NAFLD patients. This study was carried out to assess the effects of symbiotic and/or Vitamin E supplementation on liver enzymes, leptin, lipid profile, and some parameters of insulin resistance (IR) in NAFLD patients.Materials and Methods:We randomly assigned sixty NAFLD adult patients to receive (1) symbiotic tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Intriguingly, the effects of this symbiotic on NAFLD have also been recently evaluated in three additional pilot RCTs with conflicting results [ 110 , 111 , 112 ]. Thus, in a study carried out with 74 overweight and obese volunteers who did not undergo dietary and physical exercise programmes, one capsule per day of this multi-ingredient significantly decreased the severity of hepatic steatosis (analysed by ultrasonography) 8 weeks after the beginning of the treatment, fully counteracting this alteration in 50% and 25% of the participants who showed a mild and moderate degree of NAFLD at baseline, respectively [ 110 ].…”
Section: Multi-ingredient Nutritional Approaches For the Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Intriguingly, the effects of this symbiotic on NAFLD have also been recently evaluated in three additional pilot RCTs with conflicting results [ 110 , 111 , 112 ]. Thus, in a study carried out with 74 overweight and obese volunteers who did not undergo dietary and physical exercise programmes, one capsule per day of this multi-ingredient significantly decreased the severity of hepatic steatosis (analysed by ultrasonography) 8 weeks after the beginning of the treatment, fully counteracting this alteration in 50% and 25% of the participants who showed a mild and moderate degree of NAFLD at baseline, respectively [ 110 ].…”
Section: Multi-ingredient Nutritional Approaches For the Treatmentmentioning
confidence: 99%
“…Although this attenuation of fatty liver was only weakly observed in the group that received the placebo, when a direct comparison between both groups was performed, no significant changes were reported in this parameter at the end of the treatment period, and the synbiotic did not produce a significant decrease in the circulating levels of ALT, AST or CRP [ 110 ]. In another study conducted with 60 adult overweight and obese participants with NAFLD diagnosed by hepatic ultrasonography and elevated levels of ALT, Ekhlasi and co-workers analysed whether daily supplementation with this multi-ingredient (two capsules per day) plus vitamin E (400 IU/day) for 8 weeks strengthened the effects produced by the synbiotic or the vitamin E when they were administered separately [ 111 , 112 ]. Although the volunteers were not subjected to a lifestyle modification programme, the authors found that both the synbiotic and the symbiotic plus vitamin E produced a similar decrease in systolic blood pressure (SBP) and the circulating levels of TAGs and total cholesterol [ 111 , 112 ].…”
Section: Multi-ingredient Nutritional Approaches For the Treatmentmentioning
confidence: 99%
See 3 more Smart Citations